The influence of scientific approach and interactive multimedia toward students’ learning achievements and attitudes of science on human reproductive system material in man Darussalam Aceh Besar - Azhari Azhari; Khairil Khairil; Tongku Nizwan Siregar (Jurnal Edubio Tropika, 2018)
The objective of this study is to determine the improvement of students’ learning achievement and their attitudes toward science by applying the scientific approach and interactive multimedia on human reproductive system material. This research was conducted at MAN Darussalam located at Jl. Tgk Glee Iniem, No 01, Darussalam, Great Aceh from 1st to 25th May 2015. The method used is an experiment study that refers to pretest-posttest control group design. The sample in this study consists of 30 students divided into two groups; the experimental class and the control class. The sample of this study was decided by using purposive sampling technique. The parameter was the result of students’ cognitive and attitude toward science. The data were analyzed by using Gain and Normalization Gain (N-Gain), and T-Test to define the difference. The results showed that the influence of scientific and interactive multimedia approaches can improve students' learning achievement and attitude toward sciences. This can be seen from the students’ learning results with an average score of 55.48 (experimental class) and 45.32 (control class). While, the students' attitude toward science in the experimental class improved about 0.39 from which 3.06 was in the initial attitude and 3.45 was in the final attitude. On the other hand, the control class increased about 0.2 from a score of 2.9 initial attitudes to 3.1 on Student's final attitude. It showed that the implementation of scientific approaches and interactive multimedia is better than conventional methods.Keywords: Scientific and Interactive Multimedia, Learning Achievement and Attitude toward science and Human Reproductive System Material.